Kegiatan Public Relations di Perusahaan Travel Haji dan Umrah: PT Retali Mustajab Travel - Syarifah, Syifa; Qolbiyah, Fatimah Zahrotul; Nailimuna, Ratu Syakira Demi; Maria, Shafatasha (Brand Communication, 2024)
Public relations is an interaction process to create public opinion as input that benefits both parties and instills understanding, fosters motivation and public participation that determines the life of the company. In the Hajj and Umrah travel business, public relations is very important in maintaining relationships between the company and prospective pilgrims so as to increase their trust in the travel. In this research, among the public relations strategies carried out by PT Retali Mustajab Travel are establishing good relationships with prospective and alumni congregations, holding friendly events with travel partners, conducting company outreach with the community, and evaluating strategies that have been implemented.